Characterization and evaluation of the cytotoxic, antioxidant, and anti-human lung cancer properties of copper nanoparticles green-synthesized by fennel extract following the PI3K/AKT/Mtor signaling pathway - Tao Huang; KaiLi Ma; Yihua Wang (PLoS ONE, 2025)
This work established the cytotoxic, antioxidant and anticancer effects of copper nanoparticles (CuNPs) manufactured with fennel extract, especially on non-small cell lung cancer (NSCLC) as well. CuNPs caused cytotoxicity in a dose-dependent manner for two NSCLC cell lines, A549 and H1650. At 100 μg/ml, CuNPs reduced cell viability to 70% in A549 cells and 65% in H1650 cells. which showed a cytotoxic effect (p<0. 05). Lactate dehydrogenase (LDH) was correspondingly present in a high proportion in the cells, demonstrated upon testing. Together with their cytotoxic properties, CuNPs demonstrated high antioxidative activity. When the concentration of the nano particles was high (100 μg/ml), the ratio of reactive oxygen species (ROS) was reduced as much as 50%, which in turn suggested antioxidant activity. There was plenty of evidence that CuNPs had anti-cancer potential; this has been shown by the effect of the molecules on the PI3K/AKT/mTOR pathway, which was one of the pathways crucial for cancer survival. Western blot analysis and qRT-PCR results indicated a widespread degradation of the proteins in this pathway upon CuNP exposure. Interestingly, there was a declined phosphorylation up to 75% of PI3K, AKT, and mTOR at 100 μg/ml (p<0. 001). In summary, these findings illustrated the mechanisms behind the therapeutic effect of CuNPs, thus making them good targets for the NSCLC treatment. CuNPs have cytotoxic and antioxidant capacity, as well as significant alterations in lung cancers pathway, and therefore they can be considered as anti-cancer candidates.